(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Nicotinamide (NA) has shown potential benefits in acne vulgaris, photodamage, cellulite, and atopic dermatitis. Aim: In this study, a topical microemulsion based gel (MBG) of NA has been prepared. Materials and Methods: Microemulsion was composed of NA, Peppermint oil, Tween 20, and distilled water. The microemulsion was converted into MBGs using various concentrations of hydrophilic colloidal silica and Carbopol 934P. MBGs which were found to be the most stable ones were evaluated for further parameters. Results: MBGs with 4.1% hydrophilic colloidal silica and 1.1% Carbopol 934P were observed to be most stable after stability studies and were further assessed for rheology, spreadability, bioadhesion, and ex-vivo release and retention. The results connoted that MGB colloidal silica 4.1% was clear and MBG Carbopol 934P 1.1% was translucent, both with shear thinning properties. The ex vivo evaluation using pig ear skin was performed for both the gels to study the drug release and drug retention in comparison to NA solution. The release kinetics was fitted to zero-order model. The drug release and retention were higher in the following order MBG Carbopol >MBG Colloidal Silica >NA solution. Conclusion: The study indicates that MBG can be an effective system for topical delivery of NA.